The Influence of Road Quality, Service Performance, and Perception of Safety on Tourism Visit Intentions Which Are Moderate Toll Road User Satisfaction Surabaya - Probolinggo - Aziz, Aminuddin; Hwihanus, Hwihanus (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This Study aims to investigate the influence quality of the road, performance service, and perception security on intention traveling, as well role of moderating satisfaction user road in connection. Method survey used to collect data from user road Surabaya- Probolinggo toll road. Data was later analyzed using Structural Equation Modeling (SEM) through the device soft SmartPLS. Results analysis show that quality roads and performance service have a significant influence​ on intention travel. However, perception security has no significant influence.​ An interesting result​ is that satisfaction users’ road moderate connection between the quality of the road and intention traveling, as well as between performance service and intention travel. This matter shows that satisfaction with user road can strengthen or weaken the impact quality road and performance service to intended travelers. Findings This gives useful insight​ for managing road tolls and holds the interest of tourists in increasing their experience using roads and strengthening Power pulls regional tourism. With notice factors, the manager​ road toll can design more strategy​ effective to increase interest travelers in visiting traversed areas​ by road toll.